Facile Assembly of Chiral Metallosquares by Using Enantiopure Tribenzotriquinacene Corner Motifs. Issue 34 (27th July 2015) - Xu, Wen‐Rong; Xia, Guang‐Jie; Chow, Hak‐Fun; Cao, Xiao‐Ping; Kuck, Dietmar
Abstract Invited for the cover of this issue are Wen‐Rong Wu, Guang‐Jie Xia, and Hak‐Fun Chow of The Chinese University of Hong Kong, Xiao‐Ping Cao of Lanzhou University and Dietmar Kuck of Bielefeld University. The image depicts how different routes can lead to the same goal. Read the full text of the article at 10.1002/chem.201501556.